Informācijas tehnoloģijas nozares tiesību un standartu pamati - Šmite, Darja; Dosbergs, Dainis; Borzovs, Juris (LU Apgāds, 2005)
Fundamentals of laws and standards in information and communication technology sector are presented.
Keywords: information and communication technology; laws; standards